Physico-Chemical and Antifungal Investigation of Co(II), Ni(II) and Cu(II) Complexes with Schiff Bases - RAI, B.K.; BALUNI, AKHILESH; PRASAD, ANUKUL; THAKUR, R.; PRAKASH, PREM (Asian Journal of Chemistry, 2010)
A new series of complexes of Co(II), Ni(II) and Cu(II) with 2-acetyl naphtho[2-1-b]furan semicarbazone (ANFS) have been synthesized and characterized by elemental analysis, conductivity, thermal analysis, magnetic moment, IR, UV-Vis spectral studies. From the analytical data the stoichiometry of the complexes has been found of the type [M(ANFS)2]X2, where X = Cl–, Br–, I–, NO3– and ClO4–. IR spectral data suggest ligand coordinates to the metal ion through azomethine N, oxygen atom of furan ring of the ligand and carbonyl oxygen of semicarbazone. The high value of molar conductance suggests the complexes were found to be electrolytic in nature of 1:2 type. The physico-chemical data suggest that all the complexes possess octahedral geometry. The ligands as well as metal complexes are also screened for antifungal activity.